2022
DOI: 10.1002/qj.4332
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of subseasonal sea‐ice forecasts using ensemble model output statistics and observational uncertainty

Abstract: In response to a growing demand for improved sea‐ice forecast guidance at shorter timescales and higher spatial resolutions, this study investigates the predictive skill of daily subseasonal sea‐ice forecasts from two state‐of‐the‐art prediction systems: SEAS5 from the European Centre for Medium‐Range Weather Forecasts (ECMWF) and the Global Ensemble Prediction System (GEPS) of Environment and Climate Change Canada (ECCC). Based on hindcast records from 1998–2017, we find that probabilistic forecasts of sea‐ic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Information about SEAS5, Météo France, and GloSea6 is detailed in Table S1 in Supporting Information . The dynamical seasonal forecasting systems show relatively low forecast accuracy, which may be due to uncertainties in model physics (Blanchard‐Wrigglesworth et al., 2015), initial conditions (Blanchard‐Wrigglesworth et al., 2017), and model drift (Dirkson et al., 2022). By comparison, Atsicn shows a significant improvement in SIC forecast, indicating the advantages of data‐driven modeling in effectively learning the intricate and nonlinear spatiotemporal patterns of the seasonal sea‐ice system.…”
Section: Resultsmentioning
confidence: 99%
“…Information about SEAS5, Météo France, and GloSea6 is detailed in Table S1 in Supporting Information . The dynamical seasonal forecasting systems show relatively low forecast accuracy, which may be due to uncertainties in model physics (Blanchard‐Wrigglesworth et al., 2015), initial conditions (Blanchard‐Wrigglesworth et al., 2017), and model drift (Dirkson et al., 2022). By comparison, Atsicn shows a significant improvement in SIC forecast, indicating the advantages of data‐driven modeling in effectively learning the intricate and nonlinear spatiotemporal patterns of the seasonal sea‐ice system.…”
Section: Resultsmentioning
confidence: 99%
“…Bias-correction methods can be challenging in the context of a rapidly evolving sea-ice background state due to climate change, where typically skill improvement is reliant upon improving climatological bias, with the underlying assumption that previous (hindcast) bias is representative of forecast bias. Dirkson et al (2022) has demonstrated that, at least for more robust calibration methods, forecast skill can still be improved. Still, accurate assessments of uncalibrated forecast skill are necessary to assess the system for operational purposes.…”
Section: Pan-arctic Skillmentioning
confidence: 99%
“…Dirkson et al . (2022) has demonstrated that, at least for more robust calibration methods, forecast skill can still be improved. Still, accurate assessments of uncalibrated forecast skill are necessary to assess the system for operational purposes.…”
Section: Skill Of Geps Sea‐ice Forecastsmentioning
confidence: 99%
“…In sea ice forecasting, most calibration methods have been developed for subseasonal to seasonal time scales (e.g. Zhao et al, 2020;Director et al, 2021;Dirkson et al, 2019Dirkson et al, , 2022, but short-term sea ice forecasts produced by dynamical models are usually not calibrated despite their potential interests for end-users (Wagner et al, 2020). Nevertheless, Palerme and Müller (2021) showed that the errors of short-term sea ice drift forecasts (up to 10 days) from the TOPAZ4 prediction system (Sakov et al, 2012) can be significantly reduced using random forest models (by 8 % and 7 % for the direction and speed of sea ice drift, respectively).…”
Section: Introductionmentioning
confidence: 99%